Unexplored Character Diversity in Onychophora (Velvet Worms): A Comparative Study of Three Peripatid Species - Oliveira, Ivo de Sena (2012)
Low character variation among onychophoran species has been an obstacle for taxonomic and phylogenetic studies in the past, however we have identified a number of new and informative characters using morphological, molecular, and chromosomal techniques. Our analyses involved a detailed examination of Epiperipatus biolleyi from Costa Rica, Eoperipatus sp. from Thailand, and a new onychophoran species and genus from Costa Rica, Principapillatus hitoyensis gen. et sp. nov.. Scanning electron microscopy on embryos and specimens of varying age revealed novel morphological characters and character states, including the distribution of different receptor types along the antennae, the arrangement and form of papillae on the head, body and legs, the presence and shape of interpedal structures and fields of modified scales on the ventral body surface, the arrangement of lips around the mouth, the number, position and structure of crural tubercles and anal gland openings, and the presence and shape of embryonic foot projections. Karyotypic analyses revealed differences in the number and size of chromosomes among the species studied. The results of our phylogenetic analyses using mitochondrial COI and 12S rRNA gene sequences are in line with morphological and karyotype data. However, our data show a large number of unexplored, albeit informative, characters in the Peripatidae. We suggest that analysing these characters in additional species would help unravel species diversity and phylogeny in the Onychophora, and that inconsistencies among most diagnostic features used for the peripatid genera in the literature could be addressed by identifying a suite of characters common to all peripatids.